2020
DOI: 10.1007/s12178-020-09625-z
|View full text |Cite
|
Sign up to set email alerts
|

Robots in the Operating Room During Hip and Knee Arthroplasty

Abstract: Purpose of the Review The utilization of technology has increased over the last decade across all surgical specialties. Roboticassisted surgery, among the most advanced surgical technology, applied to hip and knee arthroplasty has experienced rapid growth in utilization, surgical applications, and robotic platforms. The goal of this study is to provide a comprehensive review of the most commonly utilized robotic platforms for hip and knee arthroplasty and the most up to date literature on the benefits and limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 66 publications
(78 reference statements)
0
42
0
Order By: Relevance
“…Several studies have shown improved accuracy in implant positioning and limb alignment with the use of robotic arms in TKA procedures [ [25] , [26] , [27] , [28] , [29] , [30] ]. However, potential concerns associated with using robotic arms for TKA include increased costs, increased surgical time, and no guarantee of improved accuracy or decreased postoperative complications [ [30] , [31] , [32] , [33] ]. Despite contrasting views and evidence in regard to robotics in TKA, utilization of robot arm–assisted TKA has been rapidly growing, with a reported 6.8% increase in usage between 2005 and 2014 [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown improved accuracy in implant positioning and limb alignment with the use of robotic arms in TKA procedures [ [25] , [26] , [27] , [28] , [29] , [30] ]. However, potential concerns associated with using robotic arms for TKA include increased costs, increased surgical time, and no guarantee of improved accuracy or decreased postoperative complications [ [30] , [31] , [32] , [33] ]. Despite contrasting views and evidence in regard to robotics in TKA, utilization of robot arm–assisted TKA has been rapidly growing, with a reported 6.8% increase in usage between 2005 and 2014 [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are still several limitations of robotic THA: installation costs, additional radiation exposure, learning curve, and the compatibility of the robotic systems with a limited number of implants [ 48 ]. While there is growing evidence that robotic-assisted UKA may improve clinical outcomes and implant survivorship [ 31 , 37 , 49 ], recent reviews and meta-analyses encompassing patients undergoing robotic-assisted THA reach a similar previous conclusion [ 50 54 ]. Whether semi-active or fully-active robotic systems are effective in improving postoperative pain, quality of life, and satisfaction following THA is unclear; thus further research is needed to determine if better outcomes and improved implant longevity could justify increased costs.…”
Section: Robotic Total Hip Arthroplastymentioning
confidence: 71%
“…As long-term outcomes become clearer, surgeons will need to decide whether the risks and benefits of adopting such technology outweigh those associated with the freedom of implant choice. 31 , 32 …”
Section: Robotic Systemsmentioning
confidence: 99%